A phase 1 study of inotuzumab ozogamicin in pediatric relapsed/refractory acute lymphoblastic leukemia (ITCC-059 study) - Brivio, Erica; Locatelli, Franco; Lopez-Yurda, Marta; Malone, Andrea; Díaz-de-Heredia, Cristina; Bielorai, Bella; Rossig, Claudia; van der Velden, Vincent H J; Ammerlaan, Anneke C J; Thano, Adriana; van der Sluis, Inge M; den Boer, Monique L; et al. (Blood, 2021)
This phase 1 study investigated the recommended phase 2 dose (RP2D) of inotuzumab ozogamicin (InO), a CD22-directed antibody-drug conjugate, in pediatric patients with multiple relapsed/refractory (R/R) CD22+ acute lymphoblastic leukemia (ALL). Patients (age ≥1 year or <18 years) received 3 doses of InO (days 1, 8, and 15) per course. Dose escalation was based on dose-limiting toxicities (DLTs) during course 1. Dose level 1 (DL1) was 1.4 mg/m2 (0.6, 0.4, 0.4 mg/m2) and DL2 was 1.8 mg/m2 (0.8, 0.5, 0.5 mg/m2). Secondary end points included safety, antileukemic activity, and pharmacokinetics. Twenty-five patients (23 evaluable for DLTs) were enrolled. In course 1, the first cohort had 1 of 6 (DL1) and 2 of 5 (DL2) patients who experienced DLTs; subsequent review considered DL2 DLTs to be non-dose-limiting. Dose was de-escalated to DL1 while awaiting protocol amendment to re-evaluate DL2 in a second cohort, in which 0 of 6 (DL1) and 1 of 6 (DL2) patients had a DLT. Twenty-three patients experienced grade 3 to 4 adverse events; hepatic sinusoidal obstruction syndrome was reported in 2 patients after subsequent chemotherapy. Overall response rate after course 1 was 80% (95% confidence interval [CI], 59% to 93%) (20 of 25 patients; DL1: 75% [95% CI, 43% to 95%], DL2: 85% [95% CI, 55% to 98%]). Of the responders, 84% (95% CI, 60% to 97%) achieved minimal residual disease (MRD)-negative complete response, and 12-month overall survival was 40% (95% CI, 25% to 66%). Nine patients received hematopoietic stem cell transplantation or chimeric antigen receptor T cells after InO. InO median maximum concentrations were comparable to simulated adult concentrations. InO was well tolerated, demonstrating antileukemic activity in heavily pretreated children with CD22+ R/R ALL. RP2D was established as 1.8 mg/m2 per course, as in adults. This trial was registered at https://www.clinicaltrialsregister.eu as EUDRA-CT 2016-000227-71.
Keywords: Antineoplastic Agents, Immunological; Neoplasm Recurrence, Local; Infant; Male; lidé; Treatment Outcome; Humans; Child; Child, Preschool; lokální recidiva nádoru; mužské pohlaví; výsledek terapie; Inotuzumab Ozogamicin; kojenec; akutní lymfatická leukemie; inotuzumab ozogamicin; dítě; protinádorové látky imunologicky aktivní; Precursor Cell Lymphoblastic Leukemia-Lymphoma; ženské pohlaví; Female; předškolní dítě